The Success and Failure of Mergers & Acquisitions in technology industries. A strategic analysis of an Aerospace and Defence multinational. - Aitken, Tom (2017)
Due to an intense rise in Mergers and Acquisitions (M&A’s) over the past few decades, external growth strategies have become commonplace, particularly within increasingly competitive high-tech industries. Failure to achieve growth leaves firms behind the curve, and potentially risks them being acquired by a larger organisation. However, a paradox exists whereby despite the increase in M&A’s, they reportedly have high failure rates. Many fail to achieve expected synergies, and there is not yet consensus in the literature to provide a definitive model for growth through M&A’s. The complexity of the acquisition process has resulted in a major research focus in recent years investigating financial, strategic, cultural, and operational aspects; especially in high-tech industries. The current piece of work examines the reasons why firms engage in M&A’s, how they carry them out, and addresses their failure rate in a number of industries. Subsequently, there is an analysis at firm level involving a recent acquisition made by Leonardo, an Aerospace and Defence Multinational Enterprise; in which pre-acquisition expectations (financial and strategical) are compared to actual performance, using historical data and interviews. Findings suggest that firm acquisition processes would benefit from thorough pre-acquisition screening, clear rationale, and realistic expectation setting both financially and strategically. Additionally, the paper offers insights into acquisition management, finding that firms should implement a clear integration process to manage culture and retain key staff. Finally, this research suggests that more needs to be done by firms to effectively monitor post-acquisition progress, maintaining and enhancing performance.